POLA HUBUNGAN KERJA PATRON KLIEN INDUSTRI SAGU DI DESA SUNGAI TOHOR KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Nur’aini Azma; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was carried out in Sungai Tohor Village, Tebing Tinggi Timur District. The purpose of this study was to determine the characteristics of workers and employers of the Sagu Industry in Sungai Tohor Village. The topic of this research focus is the pattern of Patron-client employment relationships in the Sagu Industry in Sungai Tohor Village. The technique of determining samples by purposive sampling and determining the number of samples as many as 15 people. The author uses qualitative descriptive methods and data instruments are observation, interviews and documentation. The study found that there were several characteristics of employers and workers in the Sungai Tohor Village Sagu Industry, namely as follows: Employment agreements, work agreements between Patrons and Clients are not written. Where the agreement is made on the agreement of Patron and client based on a family agreement. Work ethic, work ethic in the sagu industry is characterized by the discipline of labor time. Even though work time is not regulated by the employer, there is a great sense of responsibility for the worker to complete the product given to the employer. Wages, wages applied in the sagu industry, based on the number of products produced by workers. Social security, social security received by clients in the form of occupational health insurance and work accident insurance. Health insurance employers always pay attention to the health of workers with work done by workers not forced by the employer. work done with the ability of the worker to complete the product. Food dependents for workers are provided by the employer. while the guarantee of workplace accidents, in the event of a work accident the patron is fully responsible. not only guarantees in work but the worker gets social protection from the employer. Keywords: Patron-Client, Sagu Industry,Sungai Tohor